PENDEKATAN LIFE SKILL BERBASIS LESSON STUDY PADA MATA KULIAH STATISTIK INFERENSIAL - Rizza Megasari; Januar Kustiandi; Rizky Dwi Putri (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2017)
Inferential statistics require students to understand and be skilled in the advanced application of descriptive statistics in the parametric and non parametric drawings required by students to achieve competence in the formulation of models, the selection of analytical techniques and conclusions as well as the interpretation of the sample statistical test results within the scope of the development economy. The problems faced are the limited knowledge of students both in the level of concept and the direct implementation of statistical materials. Another problem found in the learning process is the lack of understanding of students both individually and in groups towards the use of statistical tools to suit the needs of the analysis. The objectives of this research are (1) to know the implementation of life skill approach based on lesson study, (2) to know the increase of positive character of student of inferential statistic through life skill approach based on Lesson Study. This research uses type of action research based on lesson study with qualitative descriptive approach. The research procedure is carried out for two cycles. Each cycle is carried out on a single subject to know the results that have been achieved by the research subject as a basis for improvement in the next cycle. Each cycle consists of three stages: plan, do, see. Based on of research, the implementation of life skill approach based on lesson study can be implemented well and able to improve the positive character of student. DOI: https://dx.doi.org/10.17977/UM014v10i12017p068